Differences between wild type and mutant isolate of Serratia by the amount of prodigiosin extracted and antibacterial activity against different types of bacteria - Hussam Mahmood Hasan Al-imari (World Journal of Experimental Biosciences, 2016)
The mutation was applied on Serratia marcescens (S. marcescens) to make it produce prodigiosin with a higher amount. One isolate of S. marcescens (Wild) was exposed to different kinds of antibiotics (Gentamycin 10 μg/ml) to produce mutant isolates from S. marcescen and examined to produce prodigiosin. The isolate that produced the largest amount of prodigiosin among four isolates was used for further studies. The antibacterial activity of prodigiosin produced from bacterial strains was examined against different species of bacteria, Staphylococcus, Bacillus, E. coli, and Pseudomonas.
Keywords: Antibacterial activity, Prodigiosin, Serratia marcescens